A method for preparing copper-polytrithiocyanate nanoscale enzyme based on "reduction coordination" and a colorimetric detection method for hydrogen sulfide
Copper-poly(trithiocyanate) nanozymes were prepared by reduction coordination method, and their enzyme-like activity was used for colorimetric detection of hydrogen sulfide. This method solves the problems of complex detection and insufficient sensitivity in the existing technology, and realizes a simple, rapid and highly sensitive detection.
Patent Information
- Application Number
- CN202311017435.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-08-14
AI Technical Summary
Existing methods for detecting hydrogen sulfide require complex instruments and cumbersome pretreatment procedures, and their sensitivity and response time are insufficient, making it difficult to meet the needs for rapid, simple, and highly sensitive detection.
Copper-poly(trithiocyanate) nanozymes were prepared by reduction coordination method. Their oxidase-like and peroxidase-like activities were used for colorimetric detection of hydrogen sulfide. Copper salt and trithiocyanate were directly added to the test solution to form nanozymes, and a colorimetric reaction was carried out. The absorbance was measured by ultraviolet spectrophotometer.
It enables simple, rapid, and sensitive detection of hydrogen sulfide, with a linear detection range of 0.5–20 μM and a detection limit of 0.0504 μM. It requires no complex instruments or skilled operation and is suitable for real-time monitoring.
Smart Images

Figure CN117105876B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of colorimetric detection technology, and in particular to a method for preparing copper-poly(trithiocyanate) nanozymes based on "reduction coordination" and a colorimetric detection method for hydrogen sulfide. Background Technology
[0002] In the detection and monitoring of hydrogen sulfide, the main technologies currently employed include sensors, capillary electrophoresis, high-performance liquid chromatography (HPLC), gas chromatography (GC), electrochemical methods, and fluorescence methods. Fluorescent probes and dyes are widely used due to their ease of operation, high sensitivity, and simple instrumentation. Most of these are organic fluorescent molecules with good sensitivity and selectivity; however, these organic fluorescent probes and dyes involve a cumbersome synthesis process. Other detection methods, due to their inherent drawbacks—requiring expensive and complex instruments, complex sample pretreatment, and time-consuming processes—are limited in their application for timely and rapid detection. Therefore, providing a simple, practical, highly sensitive, accurate, and rapid method for the detection of sulfides is a pressing issue that needs to be addressed by existing technologies.
[0003] This method is more ideal because it does not require complex instruments and pretreatment procedures, and it also has the advantages of short response time and low cost. More importantly, the experimental performance can be conveniently and in real time observed with the naked eye, minimizing the need for skilled operators and demonstrating high practicality. Therefore, colorimetric methods have aroused widespread interest in sulfide detection.
[0004] Colorimetric methods generally refer to analytical methods that use a spectrophotometer to determine the content of a substance by observing the intensity of its color in a colored solution. They offer advantages such as ease of operation and rapid testing. Nanozyme colorimetry primarily works by catalytically oxidizing a chromogenic substrate. A UV spectrophotometer is then used to establish the relationship between the concentration of the analyte and the color change, thereby achieving qualitative or quantitative analysis. Nanozyme-mediated colorimetry has been widely applied to the colorimetric determination of target substances in food and the detection of heavy metal ions in the environment. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing copper-poly(trithiocyanate) nanozymes based on "reduction coordination" and a colorimetric detection method for hydrogen sulfide. The copper-poly(trithiocyanate) nanozymes prepared using the method provided by this invention exhibit excellent oxidase-like and peroxidase-like activities. Using them as nanozymes for colorimetric detection of hydrogen sulfide has the advantages of simple operation, strong practicality, high sensitivity and accuracy, and speed.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing copper-poly(trithiocyanate) nanozymes based on "reduction coordination", comprising the following steps: Copper salt solution and trithiocyanate solution were mixed and a coordination reaction was carried out to obtain copper-polytrithiocyanate nanozyme.
[0007] Preferably, the molar ratio of the copper salt to trithiocyanate is 1:0.5.
[0008] Preferably, the coordination reaction takes 3 to 8 minutes.
[0009] The present invention also provides a method for preparing copper-poly(trithiocyanate) nanozymes according to the above technical solution.
[0010] This invention also provides a colorimetric detection method for hydrogen sulfide using the copper-poly(trichlorothiocyanate) nanoenzyme described above. The method includes the following steps when using the oxidase-like activity of the copper-poly(trichlorothiocyanate) nanoenzyme for colorimetric detection of hydrogen sulfide: (1) Sodium sulfide solutions of varying concentrations were mixed with copper salt solution, trithiocyanate solution, 3,3',5,5'-tetramethylbenzidine (TMB), and acetate-sodium acetate buffer solution, respectively, and a colorimetric reaction was carried out to obtain standard solutions of sodium sulfide at each concentration. The absorbance of each standard solution at 652 nm was measured; A standard curve was plotted with the concentration of sodium sulfide solution on the x-axis and the corresponding absorbance on the y-axis to obtain the linear regression equation. (2) The absorbance of the test solution is obtained by the method of obtaining absorbance in step (1) and a colorimetric reaction is performed to obtain the absorbance of the test solution at 652 nm. The absorbance of the test solution is then substituted into the linear regression equation in step (1) to obtain the concentration of hydrogen sulfide in the test solution. Unlike the step of colorimetric detection of hydrogen sulfide using the oxidase-like activity of the copper-poly(trisulfocyanate) nanoenzyme, when colorimetric detection of hydrogen sulfide using the peroxidase-like activity of the copper-poly(trisulfocyanate) nanoenzyme is performed, hydrogen peroxide is added to the system solution to be reacted before the colorimetric reaction in steps (1) and (2).
[0011] Preferably, the molar ratio of copper salt and trithiocyanate in step (1) is 1:0.5.
[0012] Preferably, the pH value of the acetate-sodium acetate buffer solution in step (1) is 3.0~6.5.
[0013] Preferably, before the colorimetric reaction in step (1), the concentration of TMB in the system solution to be reacted is 0.15~0.5 mM.
[0014] Preferably, the temperature of the reaction in step (1) is 15~50 ℃, and the reaction time is 3~8 min.
[0015] Preferably, before the colorimetric reaction in step (1), the concentration of H2O2 in the system solution to be reacted is 0.9~1.6 mM.
[0016] This invention provides a method for preparing copper-poly(trithiocyanate) nanozymes based on "reduction coordination". By directly mixing copper salts with trithiocyanate raw materials, Cu(II) rapidly coordinates with trithiocyanate, generating copper-poly(trithiocyanate) nanozymes with optimal enzyme activity in a very short time. As a copper-based nanozyme, it exhibits excellent oxidase-like and peroxidase-like activities. Furthermore, when using copper-poly(trithiocyanate) nanozymes for colorimetric detection of hydrogen sulfide, there is no need to prepare a catalyst (copper-poly(trithiocyanate) nanozyme) beforehand. Copper salts and trithiocyanate are directly added to the test solution, rapidly forming the copper-poly(trithiocyanate) nanozyme in the reaction system solution within a short time. The colorimetric detection method provided by this invention allows for real-time observation with the naked eye or absorbance detection, minimizing the need for skilled operators and possessing high practicality. It overcomes the shortcomings of existing technologies, such as complex processes and low sensitivity. Directly adding copper salts and trithiocyanate to the test solution allows for direct application to hydrogen sulfide. 2- The detection application is simple to operate and has the advantages of low cost and rapid detection. The results of the embodiments show that the colorimetric detection method for hydrogen sulfide based on copper-poly(trichlorothiocyanate) nanozymes provided in this invention utilizes the oxidase-like activity of copper-poly(trichlorothiocyanate) nanozymes for colorimetric detection of hydrogen sulfide, with a linear detection range of 0.5~20 μM and a detection limit of 0.0504 μM; the linear detection range using the peroxidase-like activity of copper-poly(trichlorothiocyanate) nanozymes for colorimetric detection of hydrogen sulfide is 0.1~10 μM, with a detection limit of 0.0262 μM; and it has strong anti-interference ability. The colorimetric detection method for hydrogen sulfide based on copper-poly(trichlorothiocyanate) nanozymes has high specificity and sensitivity. Attached Figure Description
[0017] Figure 1 This is a colorimetric diagram for the feasibility analysis of the copper-poly(trithiocyanate) nanoenzyme sensor prepared according to the present invention, wherein... Figure 1 In diagram 'a', we see the generation of nanozymes and their multi-enzyme activity. Figure 1 In the middle b, the ultraviolet absorption spectra of copper-poly(trithiocyanate) nanomaterials catalyzing TMB color development and other different substances are shown. Figure 2 The copper-poly(trithiocyanate) nanozyme prepared in Example 1 of this invention and the nanozyme prepared in Comparative Example 1 are compared with those prepared by S. 2-Scanning electron microscope image of the damaged copper-poly(trichlorothiocyanate) complex, in which... Figure 2 In example 'a', the example '1' is used. Figure 2 In the middle, b represents comparative example 1; Figure 3 The copper-poly(trithiocyanate) nanozyme prepared in Example 1 of this invention and the nanozyme prepared in Comparative Example 1 are compared with those prepared by S. 2- Transmission electron microscopy (TEM) image of the damaged copper-poly(trichlorothiocyanate) complex, in which... Figure 3 In example 'a', the example '1' is used. Figure 3 The small image in the upper right corner of image a is the region electron diffraction pattern. Figure 3 In the example, b and c are both comparative examples 1; Figure 4 The copper-poly(trithiocyanate) nanozyme prepared in Example 1 of this invention and the nanozyme prepared in Comparative Example 1 are compared with those prepared by S. 2- X-ray diffraction patterns of the destroyed copper-poly(trithiocyanate) complex, where a is Example 1 and b is Comparative Example 1. Figure 5 The image shows the X-ray photoelectron spectrum of the copper-poly(trichlorothiocyanate) complex of the copper-poly(trichlorothiocyanate) nanozyme prepared in Example 1 of this invention. Figure 5 In the diagram, 'a' represents the energy spectrum of elemental C. Figure 5 In the diagram, b represents the energy spectrum of nitrogen elemental analysis. Figure 5 c represents the energy spectrum of elemental S. Figure 5 In the diagram, d represents the energy spectrum of Cu elemental analysis. Figure 6 This is a comparison diagram of the oxidase-like and peroxidase-like activities of copper-poly(trithiocyanate) nanozymes formed by coordination of different copper salts (including copper chloride, copper acetate, copper sulfate, and copper nitrate) with trithiocyanate in this invention. Figure 7 Different transition metal ions (Cu) in this invention 2+ Mg 2+ Zn 2+ Mn 2+ Co 2+ Ni 2+ Fe 2+ Fe 3+ Ag + and Pt 2+ Comparison of oxidase-like and peroxidase-like activities of metal-based complexes formed with trithiocyanate; Figure 8 This is a comparison diagram of the oxidase-like and peroxidase-like activities of the complexes formed by copper ions with three different ligands (including TTCA, MA, and CA). Figure 9This is a comparison diagram of the oxidase-like and peroxidase-like activities of the copper-poly(trithiocyanate) nanozyme in this invention under different pH and temperature conditions. Figure 9 In the text, 'a' represents different pH conditions. Figure 9 b represents different temperature conditions; Figure 10 This is a diagram showing the essential enzyme activity of the copper-poly(trithiocyanate) nanozyme in this invention, which catalyzes the oxidation of TMB by O2 and H2O2. Figure 10 In the figure, 'a' represents the enzyme reaction rate at different TMB concentrations. Figure 10 In the middle, b represents Lineweaver–Burk plots for different TMB concentrations. Figure 10 In this context, 'c' represents the enzyme reaction rate under different H2O2 concentrations. Figure 10 In the figure, d represents the Lineweaver–Burk plot for different H2O2 concentrations. Figure 11 The graph shows the sensitivity test results of the copper-poly(trithiocyanate) nanozyme to hydrogen sulfide in this invention. Figure 11 Figure a shows the sensitivity test results of the copper-poly(trithiocyanate) nanozyme to hydrogen sulfide. Figure 11 In section b, the absorbance and S0 are measured to assess the sensitivity of the copper-poly(trithiocyanate) nanozyme to hydrogen sulfide using its oxidase-like activity. 2- Linear correlation plot of concentration, Figure 11 In Figure c, the sensitivity test results for hydrogen sulfide using the peroxidase-like activity of copper-poly(trithiocyanate) nanozymes are presented. Figure 11 In section d, the absorbance and S0 are measured to assess the sensitivity of the copper-poly(trithiocyanate) nanozyme to hydrogen sulfide using its peroxidase-like activity. 2- Linear correlation plot of concentration; Figure 12 The figure shows the test results of the specificity of the copper-poly(trithiocyanate) nanozyme for hydrogen sulfide in this invention. Figure 12 In Figure a, the specificity test for hydrogen sulfide using the oxidase-like activity of copper-poly(trithiocyanate) nanozymes is shown. Figure 12 Figure b shows the specificity test for hydrogen sulfide using the peroxidase-like activity of copper-poly(trithiocyanate) nanozymes. Detailed Implementation
[0018] This invention provides a method for preparing copper-poly(trithiocyanate) nanozymes based on "reduction coordination", comprising the following steps: Copper salt and ultrapure aqueous solution of trithiocyanate were mixed and subjected to a coordination reaction to obtain copper-polytrithiocyanate nanozyme.
[0019] Unless otherwise specified, all raw materials used in this invention are commercially available products in the art.
[0020] In this invention, the copper salt in the copper salt solution is preferably one or more of copper chloride, copper acetate, copper sulfate, copper nitrate, and copper sulfate.
[0021] In this invention, the concentration of copper salt in the copper salt solution is preferably 0.5 mM. In this invention, the concentration of trithiocyanate in the trithiocyanate solution is preferably 0.5 mM. In this invention, the molar ratio of copper salt in the copper salt solution to trithiocyanate in the trithiocyanate solution is preferably 1:0.5. This invention controls the molar ratio of copper salt and trithiocyanate within the above range to promote sufficient coordination reaction between the two, resulting in a copper-poly(trithiocyanate) nanozyme exhibiting excellent oxidase-like and peroxidase-like activities.
[0022] In this invention, the coordination reaction time is preferably 3-8 min, more preferably 4-7 min, and even more preferably 5 min. By controlling the coordination reaction time within the above range, this invention promotes sufficient coordination between the two components, resulting in copper-poly(trithiocyanate) nanozymes exhibiting excellent oxidase-like and peroxidase-like activities.
[0023] After the coordination reaction is completed, the products of the coordination reaction are sequentially centrifuged, washed, and dried to obtain copper-poly(trithiocyanate) nanozyme. In this invention, the centrifugation speed is preferably 15000 rpm; the centrifugation time is preferably 5 minutes. This invention achieves solid-liquid separation through centrifugation. In this invention, the washing reagent is preferably ultrapure water. This invention does not have a special limitation on the number of washing cycles; washing is sufficient until the supernatant is colorless. This invention removes residual reagents through washing. In this invention, the drying method is preferably vacuum drying; the drying temperature is preferably 80 °C; the drying time is preferably 3 hours. This invention removes residual moisture through drying.
[0024] The present invention also provides a method for preparing copper-poly(trithiocyanate) nanozymes according to the above technical solution.
[0025] In this invention, the copper-poly(trithiocyanate) nanozyme is preferably composed of monovalent copper and poly(trithiocyanate).
[0026] In this invention, the copper-poly(trithiocyanate) nanozyme is in an amorphous form and has a spherical structure.
[0027] This invention also provides a colorimetric detection method for hydrogen sulfide using the copper-poly(trichlorothiocyanate) nanoenzyme described above. The method includes the following steps when using the oxidase-like activity of the copper-poly(trichlorothiocyanate) nanoenzyme for colorimetric detection of hydrogen sulfide: (1) Sodium sulfide solutions of varying concentrations were mixed with copper salt solution, trithiocyanate solution, TMB and acetic acid-sodium acetate buffer solution respectively, and colorimetric reactions were carried out to obtain standard solutions of sodium sulfide at each concentration. The absorbance of each standard solution at 652 nm was measured; A standard curve was plotted with the concentration of sodium sulfide solution on the x-axis and the corresponding absorbance on the y-axis to obtain the linear regression equation. (2) The absorbance of the test solution is obtained by the method of obtaining absorbance in step (1) and a colorimetric reaction is performed to obtain the absorbance of the test solution at 652 nm. The absorbance of the test solution is then substituted into the linear regression equation in step (1) to obtain the concentration of hydrogen sulfide in the test solution. Unlike the step of colorimetric detection of hydrogen sulfide using the oxidase-like activity of the copper-poly(trisulfocyanate) nanoenzyme, when colorimetric detection of hydrogen sulfide using the peroxidase-like activity of the copper-poly(trisulfocyanate) nanoenzyme is performed, hydrogen peroxide is added to the system solution to be reacted before the colorimetric reaction in steps (1) and (2).
[0028] In this invention, sodium sulfide solutions of varying concentrations are mixed with copper salt solutions, trithiocyanate solutions, TMB, and acetate-sodium acetate buffer solutions to produce colorimetric reactions, thereby obtaining standard solutions of sodium sulfide at various concentrations.
[0029] In this invention, the molar ratio of copper salt to trithiocyanate is preferably 1:(0.4~2), more preferably 1:(0.5~0.15). This invention controls the molar ratio of copper salt to trithiocyanate within the above range to promote sufficient coordination reaction between the two, resulting in copper-polytrithiocyanate nanozymes exhibiting excellent oxidase-like and peroxidase-like activities.
[0030] In this invention, the pH value of the acetate-sodium acetate buffer solution is preferably 3.0~6.5, more preferably 3.5~5. In this invention, when using the oxidase-like activity of the copper-poly(trisulfuric acid) nanoenzyme for colorimetric detection of hydrogen sulfide, the pH value of the acetate-sodium acetate buffer solution is further preferably 3.5; when using the peroxidase-like activity of the copper-poly(trisulfuric acid) nanoenzyme for colorimetric detection of hydrogen sulfide, the pH value of the acetate-sodium acetate buffer solution is further preferably 4.
[0031] In this invention, before the colorimetric reaction, the concentration of TMB in the system solution to be reacted is preferably 0.15~0.5 mM, more preferably 0.2~0.4 mM, and even more preferably 0.3 mM. This invention controls the concentration of 3,3',5,5'-tetramethylbenzidine in the system solution to be reacted to be within the above range before the colorimetric reaction, so that the absorbance after the colorimetric reaction conforms to Beer-Lambert's law, which is beneficial for the subsequent quantitative analysis of hydrogen sulfide.
[0032] In this invention, the detection temperature of the display reaction is preferably 15~50 °C, more preferably 25 °C; the display reaction time is preferably 3~8 min. This invention controls the temperature and time of the display reaction within the above ranges, making the reaction temperature more convenient, eliminating the need for heating or cooling, and achieving optimal enzyme activity at room temperature and with a shorter detection time.
[0033] After obtaining standard solutions of sodium sulfide at various concentrations, the present invention measures the absorbance of each standard solution at 652 nm; a standard curve is plotted with the concentration of sodium sulfide solution as the abscissa and the corresponding absorbance as the ordinate, and a linear regression equation is obtained.
[0034] The present invention does not impose any special limitation on the method for obtaining the linear regression equation; any method well known in the art can be used.
[0035] After obtaining the linear regression equation, the present invention performs a colorimetric reaction on the test solution according to the above-described method for obtaining absorbance, and obtains the absorbance of the test solution at 652 nm. Substituting the absorbance into the linear regression equation, the concentration of hydrogen sulfide in the test solution is obtained.
[0036] In this invention, the concentration of hydrogen sulfide in the test solution is preferably 0.1~10 μM.
[0037] In this invention, unlike the step of colorimetric detection of hydrogen sulfide using the oxidase-like activity of the copper-poly(trisulfocyanate) nanoenzyme, when colorimetric detection of hydrogen sulfide using the peroxidase-like activity of the copper-poly(trisulfocyanate) nanoenzyme, hydrogen peroxide is added to the system solution to be reacted before the colorimetric reaction.
[0038] In this invention, the preferred step for colorimetric detection of hydrogen sulfide using the peroxidase-like activity of the copper-poly(trithiocyanate) nanozyme is as follows: (S1) Sodium sulfide solutions of varying concentrations were mixed with copper salt solution, trithiocyanate solution, TMB, acetate-sodium acetate buffer solution, and hydrogen peroxide, respectively, and a colorimetric reaction was carried out to obtain standard solutions of sodium sulfide at each concentration. The absorbance of each standard solution at 652 nm was measured; A standard curve was plotted with the concentration of sodium sulfide solution on the x-axis and the corresponding absorbance on the y-axis to obtain the linear regression equation. (S2) The test solution is subjected to a colorimetric reaction according to the method of obtaining absorbance in step (S1) to obtain the absorbance of the test solution at 652 nm. The absorbance of the test solution is then substituted into the linear regression equation in step (S1) to obtain the concentration of hydrogen sulfide in the test solution.
[0039] In this invention, before the colorimetric reaction, the concentration of H2O2 in the solution to be reacted is 0.9~1.6 mM, more preferably 1~1.4 mM, and even more preferably 1.2 mM. This invention controls the concentration of H2O2 in the solution to be reacted to be within the above range before the colorimetric reaction, so that the absorbance after the colorimetric reaction conforms to Beer-Lambert's law, which is beneficial for the subsequent quantitative analysis of hydrogen sulfide.
[0040] The colorimetric detection method provided by this invention is simple to operate, has mild reaction conditions, and is suitable for large-scale application.
[0041] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0042] Example 1 The method for preparing copper-poly(trithiocyanate) nanozymes based on "reductive coordination" includes the following steps: 80 μL of ultrapure aqueous solution of copper chloride (0.5 mM) and 40 μL of ultrapure aqueous solution of trithiocyanate (0.5 mM) were added to a 1 mL centrifuge tube. The solution color turned yellow rapidly. The complexation reaction was carried out at 25 °C for 5 min. Then the product of the complexation reaction was centrifuged at 15000 rpm for 5 min. The brick red precipitate was collected and washed several times with ultrapure water until the supernatant was colorless. Then it was vacuum dried in an oven at 80 °C for 3 hours to obtain copper-polytrithiocyanate nanozyme. The molar ratio of copper chloride to trithiocyanate is 1:0.5.
[0043] Comparative Example 1 S 2- The preparation method of the copper-poly(trithiocyanate) complex that has been damaged (or sulfided) comprises the following steps: 80 μL of an ultrapure aqueous solution of copper chloride (0.5 mM) and 40 μL of an ultrapure aqueous solution of trithiocyanate (0.5 mM) (the molar ratio of copper chloride and trithiocyanate is 1:0.5) were added to a 1 mL centrifuge tube, followed by 30 μL of Na₂S solution (1 mM). The solution quickly turned yellow. The mixture was centrifuged at 15000 rpm for 5 min, and the brown precipitate was collected. It was washed several times with ultrapure water until the supernatant was colorless, and then dried under vacuum in an oven at 80 °C for 3 hours to obtain the precipitate. 2- Destroyed copper-poly(trithiocyanate) complex (i.e., S) 2- (Copper-based complexes that compete with trithiocyanate for coordination with copper).
[0044] The copper-poly(trithiocyanate) nanozyme prepared in Example 1 and the S-coated nanozyme prepared in Comparative Example 1 2- The structural characterization of the disrupted copper-poly(trithiocyanate) complex is as follows: Scanning electron microscopy was used to observe the copper-poly(trithiocyanate) nanozyme prepared in Example 1 and the S-coated nanozyme prepared in Comparative Example 1. 2- Scanning electron microscope image of the destroyed copper-poly(trithiocyanate) complex as shown below Figure 2 As shown, where, Figure 2 In example 'a', the example '1' is used. Figure 2 In the example, b is comparative example 1, from... Figure 2 It can be seen that the copper-poly(trithiocyanate) nanozyme prepared in Example 1 has a spherical morphology, while the one prepared in Comparative Example 1 is shaped like a sphere. 2- The disrupted copper-poly(trithiocyanate) complex exhibits an irregular shape.
[0045] Transmission electron microscopy was used to observe the copper-poly(trithiocyanate) nanozyme prepared in Example 1 and the S-coated nanozyme prepared in Comparative Example 1. 2- Transmission electron microscopy image of the destroyed copper-poly(trithiocyanate) complex as shown below Figure 3 As shown, where, Figure 3 In example 'a', the example '1' is used. Figure 3 The small image in the upper right corner of image a is the region electron diffraction pattern. Figure 3 In the example, b and c are both comparative examples 1, from... Figure 3 It can be seen that the copper-poly(trichlorothiocyanate) nanozyme block structure prepared in Example 1 has a spherical morphology, and the regional electron diffraction pattern shows that the copper-poly(trichlorothiocyanate) nanozyme is amorphous; 2- The disrupted copper-poly(trithiocyanate) complex forms an irregular shape. Figure 3 c shows the presence of CuS crystals.
[0046] Figure 4 The copper-poly(trithiocyanate) nanozyme prepared in Example 1 and the S-coated nanozyme prepared in Comparative Example 1 2-X-ray diffraction patterns of the destroyed copper-poly(trithiocyanate) complex, where a is Example 1 and b is Comparative Example 1. Figure 4 As shown, the copper-poly(trithiocyanate) nanozyme is amorphous, while the sulfurized copper-poly(trithiocyanate) exhibits a good crystal form, which matches the characteristic peaks of CuS.
[0047] Figure 5 The copper-poly(trithiocyanate) nanozyme prepared in Example 1 and the S-coated nanozyme prepared in Comparative Example 1 2- The X-ray photoelectron spectrum of the destroyed copper-poly(trithiocyanate) complex is as follows: Figure 5 As shown, where, Figure 5 In the diagram, 'a' represents the elemental analysis of C. Figure 5 In the diagram, b represents the N element analysis. Figure 5 In the diagram, c represents the elemental analysis of S. Figure 5 In the diagram, d represents the elemental analysis of Cu, derived from... Figure 5 Analysis of the deconvolutioned XPS peaks of the copper-poly(trithiocyanate) nanozyme (C 1s, N 1s, S 2p, and Cu 2p) revealed a characteristic peak of copper-nitrogen coordination (Cu-N) at 400.1 eV for N 1s, with Cu-N accounting for 46.3% of the total N content. Analysis of S 2p showed characteristic peaks of disulfide bonds (SS) at 163.8 eV and 164.9 eV, with SS accounting for 27.5% of the total S content, confirming that the trithiocyanate polymerized in Example 1. Cu 2p contained only Cu. + This demonstrates that in Example 1, the valence state of copper changes from divalent to monovalent. XPS analysis confirms the generation of copper-poly(trithiocyanate) nanozymes based on a "reduction coordination" mechanism.
[0048] Investigation 1: The oxidase-like and peroxidase-like activities of copper-poly(trithiocyanate) nanozymes prepared according to the same method as in Example 1 were analyzed by ultraviolet-visible absorption spectroscopy, and the spectra of different materials were detected. The test methods are as follows: (1) Exploring the oxidase-like activity (OD) of copper-poly(trithiocyanate) nanozymes: 80 μL of copper chloride solution (0.5 mM) and 40 μL of polythiocyanate solution (0.5 mM) were added to a centrifuge tube containing 850 μL of acetate-sodium acetate buffer solution (pH = 4) and mixed well. 30 μL of TMB (10 mM) was then added and mixed again. The mixture was reacted at 25°C for 5 min. The absorbance of oxidized TMB (ox-TMB) at 652 nm before and after the reaction was measured using UV-Vis absorption spectroscopy. An absorbance-wavelength spectrum was plotted to evaluate the oxidase-like activity of the copper-polythiocyanate nanozyme, denoted as TMB+TTCA+Cu. 2+ Group.
[0049] (2) Exploring the peroxidase activity (POD) of copper-poly(trithiocyanate) nanoenzymes: 80 μL of ultrapure aqueous solution of copper chloride (0.5 mM) and 40 μL of ultrapure aqueous solution of polythiocyanate (0.5 mM) were added to a centrifuge tube containing 830 μL of pH 3.5 acetate-sodium acetate buffer solution and mixed well. Then, 30 μL of TMB (10 mM) and 20 μL of H2O2 (60 mM) were added and mixed well. The mixture was reacted at 25°C for 5 min. The absorbance of oxidized TMB (ox-TMB) at 652 nm before and after the reaction was measured using UV-Vis absorption spectroscopy. An absorbance-wavelength spectrum was plotted to evaluate the oxidase-like activity of the copper-polythiocyanate nanozyme, denoted as TMB+TTCA+Cu. 2+ +H2O2 group.
[0050] (3) Take 40 μL of trithiocyanate solution (0.5 mM) and add it to 910 μL of acetate-sodium acetate buffer solution (pH = 3.5) in a centrifuge tube and mix well. Add 30 μL of TMB (10 mM) and 20 μL of H2O2 (60 mM) and mix well. React at room temperature (25℃) for 5 min. Use UV-Vis absorption spectroscopy to test the absorbance of oxidized TMB (ox-TMB) in the solution before and after the reaction at 652 nm. Plot the absorbance-wavelength spectrum and record it as TMB+TTCA+H2O2 group. (4) Take 40 μL of trithiocyanate solution (0.5 mM) and add it to a centrifuge tube containing 930 μL of acetate-sodium acetate buffer solution with pH = 4. Mix well, add 30 μL of TMB (10 mM) and mix well. React at room temperature of 25℃ for 5 min. Use UV-Vis absorption spectroscopy to test the absorbance of oxidized TMB (ox-TMB) in the solution before and after the reaction at 652 nm. Plot the absorbance-wavelength spectrum and record it as TMB+TTCA group.
[0051] (5) Take 80 μL of copper chloride solution (0.5 mM) and add it to a centrifuge tube containing 860 μL of acetate-sodium acetate buffer solution at pH = 3.5. Mix well, add 30 μL of TMB (10 mM) and 20 μL of H2O2 (60 mM) and mix well. React at room temperature (5℃) for 5 min. Use UV-Vis absorption spectroscopy to measure the absorbance of oxidized TMB (ox-TMB) in the solution before and after the reaction at 652 nm. Plot the absorbance-wavelength spectrum and denote it as TMB+Cu 2+ +H2O2 group.
[0052] (6) Take 80 μL of copper chloride solution (0.5 mM) and add it to a centrifuge tube containing 890 μL of acetate-sodium acetate buffer solution at pH = 4. Mix well, add 30 μL of TMB (10 mM) and mix well. React at room temperature (5℃) for 5 min. Use UV-Vis absorption spectroscopy to measure the absorbance of oxidized TMB (ox-TMB) in the solution before and after the reaction at 652 nm. Plot the absorbance-wavelength spectrum and denote it as TMB+Cu 2+ Group.
[0053] (7) Add 30 μL of TMB (10 mM) and 20 μL of H2O2 (60 mM) to a centrifuge tube containing 950 μL of pH = 4 acetate-sodium acetate buffer solution, mix well, react at room temperature of 5℃ for 5 min, and use UV-Vis absorption spectroscopy to test the absorbance of oxidized TMB (ox-TMB) in the solution before and after the reaction at 652 nm, and draw an absorbance-wavelength spectrum, which is recorded as TMB+H2O2 group.
[0054] (8) Add 30 μL of TMB (10mM) to a centrifuge tube containing 970 μL of pH = 4 acetic acid-sodium acetate buffer solution, mix well, react at room temperature of 5℃ for 5 min, and use UV-Vis absorption spectroscopy to test the absorbance of oxidized TMB (ox-TMB) in the solution before and after the reaction at 652 nm, and draw an absorbance-wavelength spectrum, which is recorded as the TMB group.
[0055] The absorbance-wavelength diagrams of the above 8 groups were summarized to obtain the ultraviolet absorption spectra of copper-poly(trichlorothiocyanate) nanomaterials catalyzing TMB color development and other different substances, as shown below. Figure 1 As shown in b, Figure 1 In diagram 'a', nanozyme generation and its multi-enzyme activity are shown. Figure 1 It can be seen that the addition of copper-poly(trithiocyanate) nanomaterials can significantly catalyze the color development of TMB.
[0056] Investigation 2: The linear detection range and detection limit of the copper-poly(trithiocyanate) nanozyme prepared according to the same method as in Example 1 for hydrogen sulfide were analyzed by UV-Vis absorption spectroscopy. (Sulfide ions exist in the form of hydrogen sulfide under acidic conditions.) The test method is as follows: (1) Utilizing the oxidase-like activity of copper-polythiocyanate nanozyme: 20 μL of sodium sulfide solutions of varying concentrations (0.025, 0.05, 0.15, 0.25, 0.35, 0.5, 0.65, 0.75, 0.85, 1 mM), 80 μL of copper chloride solution (0.5 mM), 40 μL of thiocyanate solution (0.5 mM), 30 μL of 3,3',5,5'-tetramethylbenzidine solution (10 mM), and 830 μL of acetate-sodium acetate buffer solution at pH=4 (0.2 M) were mixed and subjected to a colorimetric reaction at room temperature for 5 min to obtain standard solutions of sodium sulfide at various concentrations; The linear changes in absorbance of each standard solution at 652 nm before and after the reaction were detected using a UV-Vis absorption spectrometer. The results showed that the linear detection range of hydrogen sulfide by colorimetric detection using the oxidase-like activity of copper-poly(trithiocyanate) nanozyme was 0.5–20 μM, and the detection limit was 0.0504 μM.
[0057] (2) The peroxidase-like activity of copper-poly(trisulfocyanate) nanozymes differs from the above-mentioned operation process of using copper-poly(trisulfocyanate) nanozymes in that H2O2 is added to the system solution to be reacted before the colorimetric reaction, and the concentration of H2O2 in the system solution to be reacted is 1.2 mM. The linear change of absorbance of each standard solution at 652 nm before and after the reaction is detected by UV-Vis absorption spectrometer. It is found that the linear detection range of hydrogen sulfide colorimetric detection using the peroxidase-like activity of copper-poly(trisulfocyanate) nanozymes is 0.1~10 μM, and the detection limit is 0.0262 μM.
[0058] Investigation 3: The oxidase-like and peroxidase-like activities of copper-poly(trithiocyanate) nanozymes formed by coordination of different copper salts (including copper chloride, copper acetate, copper sulfate, and copper nitrate) with trithiocyanate were evaluated using ultraviolet-visible absorption spectroscopy. The steps are as follows: (1) Detection of oxidase activity (OD): According to the different molar ratios of copper salt and trithiocyanate mentioned above (1:0, 1:0.67, 1:1, 1:2), ultrapure aqueous solutions of the different copper salts and trithiocyanate were added to 1 mL centrifuge tubes, followed by the addition of 0.2 M acetate-sodium acetate buffer (pH = 4) and 30 μL of TMB (10 mM). The colorimetric reaction was carried out at room temperature for 5 min, and the absorbance of the corresponding colorimetric reaction products at 652 nm was measured.
[0059] (2) Detection of peroxidase activity (POD): According to the different molar ratios of copper salt and trithiocyanate mentioned above (1:0, 1:0.67, 1:1, 1:2), ultrapure aqueous solutions of the different copper salts and trithiocyanate were added to 1 mL centrifuge tubes. Then, 0.2 M acetate-sodium acetate buffer solution (pH = 3.5), 30 μL of TMB (10 mM), and 20 μL of H2O2 (60 mM) were added. The colorimetric reaction was carried out at room temperature for 5 min, and the absorbance of the corresponding colorimetric reaction products at 652 nm was measured.
[0060] A comparison of the oxidase-like and peroxidase-like activities of copper-poly(trithiocyanate) nanozymes formed by coordination of different copper salts (including copper chloride, copper acetate, copper sulfate, and copper nitrate) with trithiocyanate is shown in the figure below. Figure 6 As shown, by Figure 6 It can be seen that there is no significant difference in enzyme activity after different copper salts react with trithiocyanate, and the form of copper salt has no effect on enzyme activity.
[0061] Investigation 4: Evaluation of different transition metal ions (Cu) using ultraviolet-visible absorption spectroscopy. 2+ Mg 2+ Zn 2+ Mn 2+ Co 2+ Ni 2+ Fe 2+ Fe 3+ Ag + and Pt 2+ The steps for determining the oxidase-like and peroxidase-like activities of the metal-based complex formed with trithiocyanate are as follows: The transition metal salt raw materials corresponding to the different transition metal ions mentioned above are CuCl2·2H2O, MgSO4, ZnCl2, Mn(Ac)2, CoCl2·6H2O, Ni(Ac)2·4H2O, FeCl2·4H2O, FeCl3·6H2O, AgNO3, and PtH2Cl6, respectively. (1) Oxidase-like activity (OD): The different transition metal ions and trithiocyanate molar ratios were 1:0, 1:0.5, 1:1 and 1:2, respectively. The different transition metal salt solutions and TTCA solutions were added to 1 mL centrifuge tubes, followed by 0.2 M acetate-sodium acetate buffer at pH = 4 and 30 μL of TMB (10 mM). The color reaction was carried out at room temperature for 5 min, and the absorbance of the corresponding color reaction products at 652 nm was measured.
[0062] (2) Peroxidase-like activity (POD): According to the different molar ratios of transition metal ions and trithiocyanate (1:0, 1:0.5, 1:1, and 1:2), the different transition metal salt solutions and TTCA solutions were added to 1 mL centrifuge tubes. Then, 0.2 M acetate-sodium acetate buffer (pH = 3.5), 30 μL of TMB (10 mM), and 20 μL of H2O2 (60 mM) were added. The colorimetric reaction was carried out at room temperature for 5 min, and the absorbance of the corresponding colorimetric reaction products at 652 nm was measured.
[0063] Different transition metal ions (Cu) 2+ Mg 2+ Zn 2+ Mn 2+ Co 2+ Ni 2+ Fe 2+ Fe 3+ Ag + and Pt 2+ The comparison of oxidase-like and peroxidase-like activities of the metal-based complexes formed with trithiocyanate is shown in the figure below. Figure 7 As shown, by Figure 7 It can be seen that Cu 2+ The enzyme-like activity was significantly enhanced after coordination with trithiocyanate; Fe 2+ and Fe 3+ It exhibits certain Fenton-like catalytic properties, and its peroxidase-like activity does not change with coordination with trithiocyanate. The enzyme-like activities of other metal ions before and after coordination with trithiocyanate are not significant.
[0064] Investigation 5: The activities of oxidase-like and peroxidase-like complexes formed by copper ions with three different ligands (including TTCA, MA, and CA) were evaluated using UV-Vis absorption spectroscopy. The steps are as follows: (1) Oxidase (OD) activity: Copper chloride solution and TTCA solution, MA solution and CA solution were added to 1 mL centrifuge tubes according to the molar ratio of copper chloride to the above different ligands of 1:0, 1:0.3, 1:0.5, 1:0.67, 1:1, 1:2 and 1:3 respectively. Then, 0.2 M acetate-sodium acetate buffer with pH = 4 and 30 μL TMB (10 mM) were added. The color reaction was carried out at room temperature for 5 min. The absorbance of the corresponding color reaction products at 652 nm was then measured.
[0065] (2) Peroxidase (POD) activity: Copper chloride and TTCA, MA and CA were added to 1 mL centrifuge tubes at molar ratios of 1:0, 1:0.3, 1:0.5, 1:0.67, 1:1, 1:2 and 1:3, respectively. 30 μL of TMB (10 mM) and 20 μL of H2O2 (60 mM) were added to a 0.2 M acetate-sodium acetate buffer system with pH = 3.5. The color reaction was carried out at room temperature for 5 min, and the absorbance of the corresponding color reaction products at 652 nm was measured.
[0066] The comparison of oxidase-like and peroxidase-like activities of the complexes formed by copper ions with three different ligands (including TTCA, MA, and CA) is shown in the figure below. Figure 8 As shown, by Figure 8 It can be seen that the enzyme activity is significantly increased after the polymerization of copper ions and trithiocyanate, which is due to the "reductive coordination" between the two. 2+ Reduced to Cu + and coordinates with partially oxidized sodium trithiocyanate (e.g. Figure 5 c and 5d); cyanuric acid and melamine cannot remove Cu 2 + The reduction process results in low final enzyme activity.
[0067] Investigation 6: Using UV-Vis absorption spectroscopy to evaluate the oxidase-like and peroxidase-like activities of copper-poly(trithiocyanate) nanozymes formed under different pH conditions, different temperature conditions, and different concentrations of TMB and H2O2 in the reaction system solution.
[0068] (1) Oxidase-like activity: The copper chloride solution and the trithiocyanate solution were added to a centrifuge tube with a molar ratio of copper chloride to trithiocyanate of 1:0.5. TMB (10 mM) and 1 mL of pH 4 acetate-sodium acetate buffer solution were added. The color reaction was carried out at room temperature for 5 min. The absorbance of the corresponding color reaction products at 652 nm was then measured.
[0069] (2) Peroxidase activity: The copper chloride solution and the trithiocyanate solution were added to a centrifuge tube with a molar ratio of copper chloride to trithiocyanate of 1:0.5. TMB (10 mM), H2O2 (60 mM) and 1 mL of pH 4 acetate-sodium acetate buffer solution were added. The color reaction was carried out at room temperature for 5 min. The absorbance of the corresponding color reaction products at 652 nm was then measured.
[0070] (3) Following the methods in steps (1) and (2) above, the oxidase-like and peroxidase-like activities of copper-poly(trithiocyanate) nanozymes were detected under different pH conditions (3.0, 3.5, 4, 4.5, 5, 5.5, 6, 6.5), different temperature conditions (15℃, 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃), and different concentrations of TMB (0.3 mM) and H2O2 (1.2 mM) in the reaction system solution. The absorbance of the corresponding colorimetric reaction products at 652 nm was measured, and the peroxidase-like properties of the catalyst, namely copper-poly(trithiocyanate) nanozymes, were analyzed by fitting the nonlinear Michaelis-Menten equation.
[0071] A comparison of the oxidase-like and peroxidase-like activities of copper-poly(trithiocyanate) nanozymes under different pH and temperature conditions is shown in the figure. Figure 9 As shown, where, Figure 9 In the text, 'a' represents different pH conditions. Figure 9 In the text, b represents different temperature conditions, derived from... Figure 9 It is known that the optimal pH for the activity of copper-poly(trisulfocyanate) nanoenzymes is 4, and the optimal temperature is 20℃; the optimal pH for the activity of copper-poly(trisulfocyanate) nanoenzymes peroxidase is 3.5, and the optimal temperature is 20℃. The essential enzyme activity diagram of copper-poly(trithiocyanate) nanozyme catalyzing the oxidation of TMB by O2 and H2O2 is shown in the figure below. Figure 10 As shown, where, Figure 10 In the figure, 'a' represents the enzyme reaction rate at different TMB concentrations, where the oxidase activity K is... max = 0.0231; V max = 1.31 × 10 -7 Ms -1 Peroxidase-like activity K max = 0.0222; V max = 3.06 × 10 -7 Ms -1 ; Figure 10 In the middle, b represents Lineweaver–Burk plots for different TMB concentrations. Figure 10 In this context, c represents the enzyme reaction rate under different H2O2 concentrations, where K... max = 3.890; V max =8.67 × 10 -8 Ms -1 ; Figure 10 In the diagram, d represents the Lineweaver–Burk plot for different H2O2 concentrations; by Figure 10 It is known that copper-poly(trithiocyanate) has activity comparable to that of natural horseradish peroxidase and has a strong affinity for TMB.
[0072] Example 2 Based on the colorimetric detection method for hydrogen sulfide using the copper-poly(trichlorothiocyanate) nanoenzyme described in Example 1, the steps for colorimetric detection of hydrogen sulfide using the oxidase-like activity of the copper-poly(trichlorothiocyanate) nanoenzyme are as follows: (1) 20 μL of sodium sulfide solutions with gradient concentrations (0.025, 0.05, 0.15, 0.25, 0.35, 0.5, 0.65, 0.75, 0.85, 1 mM) were mixed with 80 μL of copper chloride solution (0.5 mM), trithiocyanate solution (0.5 mM), 30 μL of TMB solution (10 mM), and 830 μL of pH = 4 acetic acid-sodium acetate buffer solution. The mixtures were subjected to a colorimetric reaction at room temperature for 5 min to obtain standard solutions of sodium sulfide at each concentration. The molar ratio of copper chloride to trithiocyanate is 1:0.5; The absorbance of each standard solution at 652 nm was measured; A standard curve was plotted with the concentration of sodium sulfide solution as the x-axis and the corresponding absorbance as the y-axis, yielding the linear regression equation y = 0.026x. (2) The absorbance of the test solution is obtained by the method of obtaining absorbance in step (1) and a colorimetric reaction is performed to obtain the absorbance of the test solution at 652 nm. The absorbance of the test solution is then substituted into the linear regression equation in step (1) to obtain the concentration of hydrogen sulfide in the test solution. The step of colorimetric detection of hydrogen sulfide using the oxidase-like activity of the copper-poly(trisulfocyanate) nanozyme differs from that of the step of colorimetric detection of hydrogen sulfide using the peroxidase-like activity of the copper-poly(trisulfocyanate) nanozyme. In the step of colorimetric detection of hydrogen sulfide using the peroxidase-like activity of the copper-poly(trisulfocyanate) nanozyme, hydrogen peroxide is added to the system solution to be reacted before the colorimetric reaction in steps (1) and (2). The specific steps are as follows: (S1) 20 μL of sodium sulfide solutions with gradient concentrations (0.005, 0.025, 0.05, 0.15, 0.20, 0.30, 0.35, 0.40, 0.45, 0.50, 0.75, 1, 1.25, 1.5 mM) were mixed with 80 μL of copper chloride solution (0.5 mM), 40 μL of trithiocyanate solution (0.5 mM), 30 μL of TMB (10 mM), 810 μL of pH 3.5 acetate-sodium acetate buffer solution (0.2 M), and 20 μL of H2O2 (60 mM) to a final volume of 1 mL. The mixture was subjected to a colorimetric reaction at room temperature for 5 min to obtain standard solutions of sodium sulfide at each concentration. The absorbance of each standard solution at 652 nm was measured; A standard curve was plotted with the concentration of sodium sulfide solution as the x-axis and the corresponding absorbance as the y-axis, yielding the linear regression equation y = 0.041x + 0.0079. (S2) The test solution is subjected to a colorimetric reaction according to the method of obtaining absorbance in step (S1) to obtain the absorbance of the test solution at 652 nm. The absorbance of the test solution is then substituted into the linear regression equation in step (S1) to obtain the concentration of hydrogen sulfide in the test solution.
[0073] The sensitivity of copper-poly(trichlorothiocyanate) nanozyme to hydrogen sulfide detection was evaluated using ultraviolet-visible absorption spectroscopy and through tests in Example 2. The test results of the sensitivity of copper-poly(trichlorothiocyanate) nanozyme to hydrogen sulfide are shown in the figure below. Figure 11 As shown, where, Figure 11 Figure a shows the sensitivity test results of the copper-poly(trithiocyanate) nanozyme to hydrogen sulfide. Figure 11 In section b, the absorbance and S0 are measured to assess the sensitivity of the copper-poly(trithiocyanate) nanozyme to hydrogen sulfide using its oxidase-like activity. 2- Linear correlation plot of concentration, Figure 11 In Figure c, the sensitivity test results for hydrogen sulfide using the peroxidase-like activity of copper-poly(trithiocyanate) nanozymes are presented. Figure 11 In section d, the absorbance and S0 are measured to assess the sensitivity of the copper-poly(trithiocyanate) nanozyme to hydrogen sulfide using its peroxidase-like activity. 2- The linear correlation plot of concentration, by Figure 11 It was found that the linear detection range for hydrogen sulfide using the oxidase-like activity of copper-poly(trichlorothiocyanate) nanozymes was 0.5–20 μM, with a detection limit of 0.0504 μM; the linear detection range for hydrogen sulfide using the peroxidase-like activity of copper-poly(trichlorothiocyanate) nanozymes was 0.1–10 μM, with a detection limit of 0.0262 μM. These results indicate that the enzyme-like activity of copper-poly(trichlorothiocyanate) nanozymes can effectively detect hydrogen sulfide in the range of 0.5–20 μM. 2- It has very high sensitivity.
[0074] Investigation 7: Evaluation of the specificity of copper-poly(trithiocyanate) nanozyme for hydrogen sulfide detection using ultraviolet-visible absorption spectroscopy. Following the method of Example 2, the anti-interference ability of the hydrogen sulfide colorimetric detection method based on the copper-poly(trithiocyanate) nanozyme in Example 1 was tested. The difference from Example 2 is that various interfering substances (NaCl, KCl, NaOH, NaI, NaCl, Na2NO2, Na2NO3, NaAc, Na2CO3, Na2SO4, methanesulfonic acid, lipoic acid, thioacetamide, methionine, cystine, cysteine, glutathione) were added in equimolar concentrations, and the effects of each interfering substance on the absorbance of the detection system were measured and analyzed.
[0075] (1) Interference test was performed using oxidase-like activity. Corresponding concentrations of interfering substances, sodium sulfide, copper chloride, and trithiocyanate were added to 1 mL of acetate-sodium acetate buffer solution at a molar ratio of 1:0.5 (40 μM and 20 μM, respectively), and 0.3 mM TMB were reacted at room temperature for 5 min. The linear change in absorbance in the solution before and after the reaction was measured using UV-Vis absorption spectroscopy to detect the interference effect of different interfering substances on the colorimetric detection of hydrogen sulfide in the detection system. (2) Interference testing was conducted using peroxidase-like activity. Corresponding concentrations of interfering substances, sodium sulfide, copper chloride, and trithiocyanate were added to 1 mL of an acetate-sodium acetate buffer solution at a molar ratio of 1:0.5 (40 μM and 20 μM, respectively), 0.3 mM TMB, and 1.2 Mm H2O2, respectively, and reacted at room temperature for 5 min. The linear change in absorbance in the solution before and after the reaction was measured using UV-Vis absorption spectroscopy to detect the interference effect of different interfering substances on the colorimetric detection of hydrogen sulfide in the detection system.
[0076] The results of the test for the specificity of copper-poly(trithiocyanate) nanozyme for hydrogen sulfide are shown in the figure below. Figure 12 As shown, where, Figure 12 In Figure a, the specificity test for hydrogen sulfide using the oxidase-like activity of copper-poly(trithiocyanate) nanozymes is shown. Figure 12 In section b, the peroxidase-like activity of copper-poly(trithiocyanate) nanozymes was specifically tested for hydrogen sulfide. Figure 12 It can be seen that the measured inorganic ions and biomolecules have no significant effect on the activity of copper-poly(trithiocyanate) nanozymes, even with S 2- Extremely similar interfering substances such as methanesulfonic acid, lipoic acid, thioacetamide, and methionine have no significant effect on the enzyme activity. Experimental results indicate that the S enzyme based on copper-poly(trithiocyanate) nanozyme... 2- The detection method has good selectivity and anti-interference ability.
[0077] In summary, the colorimetric detection method for hydrogen sulfide based on copper-poly(trichlorothiocyanate) nanozymes provided in this invention utilizes the oxidase-like activity of copper-poly(trichlorothiocyanate) nanozymes for colorimetric detection of hydrogen sulfide, with a linear detection range of 0.5–20 μM and a detection limit of 0.0504 μM; the linear detection range for hydrogen sulfide colorimetric detection using the peroxidase-like activity of copper-poly(trichlorothiocyanate) nanozymes is 0.1–10 μM, with a detection limit of 0.0262 μM; and it exhibits strong anti-interference ability. The colorimetric detection method for hydrogen sulfide based on copper-poly(trichlorothiocyanate) nanozymes provides high specificity and sensitivity. This invention provides a method for preparing copper-poly(trichlorothiocyanate) nanozymes based on "reduction coordination" and a colorimetric detection method for hydrogen sulfide. The two raw materials can be added in a certain proportion without prior preparation, and the detection is rapid, simple, and has excellent performance, providing the possibility for real-time monitoring of hydrogen sulfide pollutants and showing broad application prospects in the field of environmental monitoring.
[0078] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A colorimetric detection method for hydrogen sulfide based on copper-poly(trichlorothiocyanate) nanozyme, comprising the following steps when using the oxidase-like activity of the copper-poly(trichlorothiocyanate) nanozyme for colorimetric detection of hydrogen sulfide: (1) Sodium sulfide solutions of varying concentrations were mixed with copper salt solution, trithiocyanate solution, 3,3',5,5'-tetramethylbenzidine and acetate-sodium acetate buffer solution respectively, and colorimetric reactions were carried out to obtain standard solutions of sodium sulfide at each concentration. The absorbance of each standard solution at 652 nm was measured; A standard curve was plotted with the concentration of sodium sulfide solution on the x-axis and the corresponding absorbance on the y-axis to obtain the linear regression equation. (2) The absorbance of the test solution is obtained by the method of obtaining absorbance in step (1) and a color reaction is carried out to obtain the absorbance of the test solution at 652 nm. The absorbance of the test solution is then substituted into the linear regression equation in step (1) to obtain the concentration of hydrogen sulfide in the test solution. Unlike the step of colorimetric detection of hydrogen sulfide using the oxidase-like activity of the copper-poly(trisulfocyanate) nanozyme, when colorimetric detection of hydrogen sulfide using the peroxidase-like activity of the copper-poly(trisulfocyanate) nanozyme, hydrogen peroxide is added to the system solution to be reacted before the colorimetric reaction in steps (1) and (2). In step (1), the molar ratio of copper salt to trithiocyanate is 1:0.
5.
2. The colorimetric detection method according to claim 1, characterized in that, The pH value of the acetate-sodium acetate buffer solution in step (1) is 3.0~6.
5.
3. The colorimetric detection method of claim 1, wherein, Before the colorimetric reaction in step (1), the concentration of 3,3',5,5'-tetramethylbenzidine in the system solution to be reacted is 0.15~0.5mM.
4. The colorimetric detection method of claim 1, wherein, The temperature of the color development reaction in step (1) is 15~50℃, and the time of the color development reaction is 3~8min.
5. The colorimetric detection method according to claim 4, characterized in that, Before the colorimetric reaction in step (1), the concentration of H2O2 in the system solution to be reacted is 0.9~1.6mM.
